Implementing the TARGET Model in Physical Education: Effects on Perceived Psychobiosocial and Motivational States in Girls - Bortoli, Laura; Bertollo, Maurizio; Filho, Edson; di Fronso, Selenia; Robazza, Claudio (Frontiers in Psychology, 2017)
Grounded in achievement goal and self-determination theories, the purpose of this study was to investigate the effects of mastery and performance climate interventions on students’ psychobiosocial (PBS) states and self-determined motivation. A first study was conducted to determine the validity of the measures. In a second study, two groups of female students (N = 65, 14-15 years of age) took part in the investigation. A mastery-performance group participated in eight task-involving lessons and then in another set of eight ego-involving lessons. A performance-mastery group participated in ego-involving lessons and then in task-involving lessons. Findings revealed that the program was effective in changing PBS states and self-determined motivation in the performance-mastery group. In particular, participants in this group reported lower scores on pleasant/functional PBS states and self-determined motivation after the first phase of the intervention. Furthermore, lower levels of self-determined motivation were maintained after the second phase of the intervention, thereby suggesting detrimental carryover effects.